Invasive fungal infections in endogenous Cushing's syndrome - Rafael Selbach Scheffel; José Miguel Dora; Letícia Schwerz Weinert; Valério Aquino; Ana Luiza Maia; Luis Henrique Canani; Luciano Z. Goldani (MDPI AG, 2010)
Cushing's syndrome is a condition characterized by elevated cortisol levels that can result from either augmented endogenous production or exogenous administration of corticosteroids. The predisposition to fungal infections among patients with hypercortisolemia has been noted since Cushing's original description of the disease. We describe here a patient with endo-genous Cushing's syndrome secondary to an adrenocortical carcinoma, who developed concomitant disseminated cryptococcosis and candidiasis in the course of his disease.